Implementation of Pancasila Student Profile in Building the Character of SMK Students in the Field of Accounting - Febri Tunggal Marhenno; Titik Ulfatun (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2024)
The purpose of this study is to create the character of students of the accounting program and the expertise of teachers at SMK N 1 Purwodadi, the current research seeks to study the application of strengthening of student profiles Pancasila as well as to identify the challenges faced by teachers in the project strengthening student profile Pancasilla (P5) and to detail the ways in which they cope with such challenges. In this research use qualitative methods. The location of the research is SMK N 1 Purwodadi in Danyang, Purwodadi Kec, Grobogan district, Central Java 58113. The school's address is Prince Diponegoro No. 24 Sambak. Interviews, observations, and documentation are the methods used to gather data. The student profile program of Pancasila is now available at SMK N 1 Purwodadi. To develop a better character, it is important to learn to fear the One God and to have the ability to think nobly, creatively, and critically in every productive lesson. In the middle of the semester, SMK N 1 Purwodadi organizes P5 activities for students whose work is entitled entrepreneurship projects. It gives students the opportunity to be creative and produce works that can be sold to the public. Lack of time and teacher involvement is a problem in this effort, to address this, teachers can put more emphasis on student support through social media marketing and other forms of active and participatory learning about entrepreneurship.